1992
DOI: 10.1177/00220345920710050301
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Behavior of Direct Post-and-core-restored Premolars

Abstract: Evaluation of long-term mechanical behavior of new types of restorations in clinical trials is time-consuming. A partial alternative can be found in experimental fatigue-testing, which simulates accelerated mechanical deterioration. The aim of this study was to determine the feasibility of using fatigue-testing of a complex dental restoration and to evaluate the mechanical fatigue behavior of premolar teeth restored with a titanium alloy post and an amalgam or composite core. Eighty-seven human upper premolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…Early fatigue tests focused almost exclusively on restorative materials such as amalgam and resin composites [49][50][51][52][53] . To determine the feasibility of a complex dental restoration, Huysmans et al 52) employed a fatigue testing machine (load cycling at 5 Hz frequency) to evaluate the mechanical fatigue behavior of premolar teeth restored with a titanium alloy post and an amalgam or composite core.…”
Section: Load Cycling Fatigue Test Of Prg Filler-filled Adhesivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Early fatigue tests focused almost exclusively on restorative materials such as amalgam and resin composites [49][50][51][52][53] . To determine the feasibility of a complex dental restoration, Huysmans et al 52) employed a fatigue testing machine (load cycling at 5 Hz frequency) to evaluate the mechanical fatigue behavior of premolar teeth restored with a titanium alloy post and an amalgam or composite core.…”
Section: Load Cycling Fatigue Test Of Prg Filler-filled Adhesivesmentioning
confidence: 99%
“…To determine the feasibility of a complex dental restoration, Huysmans et al 52) employed a fatigue testing machine (load cycling at 5 Hz frequency) to evaluate the mechanical fatigue behavior of premolar teeth restored with a titanium alloy post and an amalgam or composite core. The restorations showed a comparable strength reduction of about 50% of their initial strength after 10 6 cycles.…”
Section: Load Cycling Fatigue Test Of Prg Filler-filled Adhesivesmentioning
confidence: 99%
“…This approach can be justified since research has shown that composite restorations tend to fail either early, before 10,000 cycles, or very late, after 100,000 cycles. 10 If at a given stress level the sample did not fail within 10,000 cycles, the stress level for the next test sample was increased by a fixed amount of 4% of the clamped fracture strength in the present test. If failure occurred, the stress level for the next sample was decreased accordingly.…”
Section: Flexural Fatigue Testingmentioning
confidence: 99%
“…These fractures are not usually related to an impact, but result from long periods of mechanical fatigue, 11,12 most likely explained by the development of little cracks on tension concentration areas. 13 Static load tests for evaluating failures in restorations have been replaced by mechanical cycling, providing greater accuracy in simulating the loads that act on restorative materials during clinical function.…”
Section: Introductionmentioning
confidence: 99%